PURIFICATION OF KROSOK SALT (CRUDE SOLAR SALT) THROUGH RECRYSTALLIZATION METHOD WITH ADDITION OF DIFFERENT CONCENTRATIONS OF SLAKED LIME (Ca(OH2)) - Perdana Ixbal Spanton; Dewi Anggraeni (Jurusan Perikanan dan Kelautan, 2024)
Purifying krosok salt (crude solar salt) is an essential step in the food and pharmaceutical industry to ensure product quality. One of the methods used for the purification of krosok salt in this study was recrystallization, involving the addition of slaked lime (Ca(OH)2) at various concentrations. Recrystallization entails dissolving salt crystals in water, followed by filtration to separate impurities from the clean salt solution. This purified salt solution is then heated to produce purer salt crystals. The aim of this study was to analyze the quality content of salt in the yielded pure salt. The significance of this research lies in its contribution of new knowledge regarding simple traditional salt processing methods, which can yield higher-quality salt with significant economic value. In this process, Ca(OH)2 was added at concentrations of 0.1%, 0.08%, and 0.06% to assess its effect on krosok salt purification. The research methodology employed experimental methods. The study's results indicated that the NaCl level test yielded an average value of 96.7% with a C concentration of 0.06%. The highest avera-ge value of 97.686% for the degree of whiteness was observed at a C concentration of 0.1%. Magnesium content averaged 0.07% at a C concentration of 0.06%, while calcium content averaged 0.058% at the same concentration. Keywords: Krosok salt, recrystallization, betel lime, salt quality.